2021
DOI: 10.3389/fmars.2021.571796
|View full text |Cite
|
Sign up to set email alerts
|

Marine Litter Windrows: A Strategic Target to Understand and Manage the Ocean Plastic Pollution

Abstract: Windrow is a long-established term for the aggregations of seafoam, seaweeds, plankton and natural debris that appear on the ocean surface. Here, we define a “litter windrow” as any aggregation of floating litter at the submesoscale domain (<10 km horizontally), regardless of the force inducing the surface convergence, be it wind or other forces such as tides or density-driven currents. The marine litter windrows observed to date usually form stripes from tens up to thousands of meters long, with litter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 49 publications
4
35
1
Order By: Relevance
“…It is important to specify that the sampling design of this study was not arranged according to the presence of slicks, i.e., concentrations may have been even higher if trawls were conducted 100% inside the slicks, suggesting that this finding is worthy for further investigation. The importance of windrows in understanding marine litter and MPs pollution and the need for targeted windrow research has been acknowledged very recently by Cózar et al (2021), in their relative perspective article.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to specify that the sampling design of this study was not arranged according to the presence of slicks, i.e., concentrations may have been even higher if trawls were conducted 100% inside the slicks, suggesting that this finding is worthy for further investigation. The importance of windrows in understanding marine litter and MPs pollution and the need for targeted windrow research has been acknowledged very recently by Cózar et al (2021), in their relative perspective article.…”
Section: Discussionmentioning
confidence: 99%
“…These waves travel over hundreds of kilometers of ocean and could conceivably accumulate a tremendous amount of plastic. Videos posted on YouTube show dense patches of plastic debris in the coastal waters off Honduras 2, 3 (see also Figure 1A in Cozar et al, 2021). The plastic patches were in the shape of long bands.…”
Section: Discussionmentioning
confidence: 97%
“…This limited set of observations begs the question: we have demonstrated that the convergence over tidally generated internal waves can concentrate and transport plastic surface drifters, but how much floating plastic does one find in internal wave convergences and is this a regular occurrence? If internal waves regularly concentrate plastic debris, could this be exploited; could one "fish" internal wave slicks to remove plastic debris (Ruiz et al, 2020;Cozar et al, 2021)?…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the mesoscale (10-200 km) circulation in form of eddies and fronts influences the horizontal movements of particles in the open ocean (Pichel et al, 2007;Howell et al, 2012;Frère et al, 2017;Brach et al, 2018). Spatial variability of particle abundance and distribution at smaller scales (<10 km) may be due to water movements resulting from processes such as internal waves, Langmuir cells, submesoscale fronts and other related roll-like instabilities with surface convergence (Hamner and Schneider, 1986;van Sebille et al, 2020;Cózar et al, 2021;Shanks, 2021).…”
Section: Introductionmentioning
confidence: 99%